Transgene-free genome editing and RNAi ectopic application in fruit trees: Potential and limitations - Gouthu, Satyanarayana; Mandelli, Christian; Eubanks, Britt A.; Deluc, Laurent G. (Frontiers in Plant Science, 2022)
For the past fifteen years, significant research advances in sequencing technology have led to a significant increase in fruit tree genomic resources and databases with a massive number of OMICS datasets (transcriptomic, proteomics, metabolomics), helping to find associations between gene(s) and performance traits. Meanwhile, new technology tools have emerged for gain- and loss-of-function studies, specifically in gene silencing and developing tractable plant models for genetic transformation. Additionally, innovative, and adapted transformation protocols have optimized genetic engineering in most fruit trees. The recent explosion of new gene-editing tools allows for broadening the set of genetic tools for functional studies in fruit trees. Yet, the fruit tree research community has not fully embraced these new technologies to provide large-scale genome characterizations as in cereals and other staple food crops. Instead, recent research efforts in the fruit trees appear to focus on two primary translational tools: the transgene-free gene editing via Ribonucleoprotein (RNP) delivery and the ectopic application of RNA-based products in the field for crop protection. The inherent nature of the propagation system and the long juvenile phase of most fruit trees are significant justifications of the first technology. The non-GMO nature of the second is claimed to have the public favor regarding sustainability and an eco-friendlier environment for a crop production system that could potentially replace the use of chemicals. Regardless of their potential, both technologies still depend on the foundational knowledge of gene-to-trait relationships generated from basic genetic studies. Therefore, we will discuss the current status of these available tools for gene silencing and DNA-based gene editing that could be utilized for high throughput functional studies in tree crops in the near future and their potential and limitations of these technologies.